EFFICACY AND SAFETY OF INCRETIN THERAPY IN TYPE 2 DIABETES MELLITUS : THE SYSTEMATIC REVIEW - Totalia, Lely Sustantine (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Hyperglycemia is the key sign of type 2 diabetes, which is a metabolic disorder characterised by an inadequate production of insulin as well as resistance to the action of insulin. As longitudinal studies of type 2 diabetes continue to provide evidence linking improved glycemic control with a reduction in the rates of diabetes-associated complications, there is a considerable interest in the therapy of type 2 diabetes, with a focus on the development and use of new agents that exhibit improved efficacy and safety in comparison to currently available medicines. Clinical use of incretin-based medicines is growing steadily, and there are numerous additional products being developed at this time. The individual mechanisms by which dual agonism of both GLP-1 and GIP receptors may improve glycemic control require further investigation. We conducted post hoc exploratory analyses of biomarkers associated with pancreatic beta-cell function and insulin sensitivity in order to investigate the mechanisms by which tirzepatide led to greater reductions of hyperglycemia than a selective GLP-1 receptor agonist. According to the findings of this paper, a dose of 15 milligrams of tizepatide was superior in reducing HbA1c levels, despite the fact that it induced higher levels of gastrointestinal side effects.